Gametes from stem cells: Status and applications in animal reproduction. (17th October 2019) - Goszczynski, Daniel E.; Denicol, Anna C.; Ross, Pablo J.
Abstract: In vitro gamete differentiation could revolutionize animal production by decreasing generation intervals, increasing the number of gametes per animal and facilitating the dissemination of elite genetics. In addition, it could help to develop new strategies for the conservation of endangered species. The recent in vitro reconstitution of germ cell development in mice has inspired researchers to invest their best efforts into reproducing this achievement in livestock species. With this goal in mind, multiple differentiation approaches and cell sources have been evaluated. The degree of success in these evaluations varies according to the species and the stage of development studied, but, in general, partially positive results have been obtained. Evidence suggests that although functional gametes with true reproductive potential are still to be obtained, it is a matter of time before this goal is achieved.